Synthesis and Characterization of Quaternary Chalcogenide Nanomaterials: A Review Study - Huda Talib; Nabeel A. Bakr; Mohammed A. Abed (ASJ - Academic Science Journal, 2024)
For the past ten years, copper-based quaternary chalcogenide semiconductor materials have also been studied and classified in a variety of ways. The majority of research and academic works on quaternary chalcogenides are devoted to solar cell PV studies, where, as the material first gained popularity as a less expensive option in contrast to Si for Solar PV systems. . Such components have all of the desirable characteristics for becoming an effective PV material in the thin films or nanomaterials configuration, like effective and non-toxic unique materials, effective charge carrier, best possible energy band, as well as higher adsorption co-effectiveness. Cu2MIMIIX4 (where X = S or/and Se; MII = Si, Sn, and Ge; MI = Zn, Mn, Fe, Co, Ni, Cd, and Hg) is a new class of quaternary materials that has just emerged and found use in electrochemistry, thermal, sensor systems, power banks, and some other technologies. The unique combination characteristics of this class of chalcogenides, like optoelectronic and electrical; magnetic and optoelectronic; as well as thermo-electric, make their potentially useful importance for a variety of usages. Even though many of the papers have already covered the PV characteristics of such quaternary chalcogenides, this material has many various uses that remain investigated. This article touches on the multi-functional systems of novel dissimilar quaternary copper-based chalcogens, including the fabrication, the doping impact on their physical and chemical characteristic, and their use in many applications, including solar cells.